Measurement of the top quark mass in the tt͞ → lepton+jets channel from √s=8 TeV ATLAS data and combination with previous results - Alconada Verzini, María Josefina (2019)
The top quark mass is measured using a template method in the tt͞ → lepton + jets channel (lepton is e or μ) using ATLAS data recorded in 2012 at the LHC. The data were taken at a proton–proton centre-of-mass energy of √s = 8 TeV and correspond to an integrated luminosity of 20.2 fb−1. The tt͞ → lepton + jets channel is characterized by the presence of a charged lepton, a neutrino and four jets, two of which originate from bottom quarks (b). Exploiting a three-dimensional template technique, the top quark mass is determined together with a global jet energy scale factor and a relative b-to-light-jet energy scale factor. The mass of the top quark is measured to be mtop = 172.08 ± 0.39 (stat) ± 0.82 (syst) GeV. A combination with previous ATLAS mtop measurements gives mtop = 172.69 ± 0.25 (stat) ± 0.41 (syst) GeV.